ANALISIS NILAI INTRINSIK SAHAM DALAM RANGKA PELAKSANAAN PROGRAM ESOP DAN MSOP PT MNC INVESTAMA, Tbk. - , MOCHAMAD ISKANDAR ZAENAL ABIDIN SASTRA KUSUMA; , Mamduh M. Hanafi, M.B.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Basically, this study aims to estimate the intrinsic value of the shares of PT MNC Investama. in order to compare with the ESOP stock price MSOP performed using the income approach method to apply the discounted cash flows (discounted cash flow) and market data comparison approach (relative valuation). The data used consist of financial statement data Investama Tbk PT MNC for the last 5 years from 2008 to 2012. Analysis of discounted cash flow method (discounted cash flow) is done by: analysis of sales or revenue projections, projected financial statements, projected free cash flow (free cash flow), the determination of the discount rate or the expected reversal rate and the estimated value. Analysis of the comparative approach (relative valuation) begins with a search for comparable companies in the same line of business the next pick and assign the appropriate multiples or ratios of comparable companies. These multiples are used to convert the book value of the relevant variables of PT MNC Investama .. be estimated market value. Multiples or ratios used are: PER (Price Earning Ratio), PBV (Price to Book Value) and P / S (Price to Sales Ratio). The results of the study by using the method of discounted cash flow and relative valuation estimate obtained by the intrinsic value of the shares of PT MNC Investama. per December 31, 2012 ranged from Rp518 to Rp569. Assessment results using relative valuation, obtained the following results: for the estimated value of stock per share of PT MNC Investama. by using a ratio based on a PER of Rp555 and Rp287 PBV ratio P / S amounted to Rp913. The average of the three results are then given a weighting values showed that the value of the shares of PT MNC Investama. per share based on relative valuation amounted to Rp599. While calculations using discounted cash flow method is obtained by Rp 518 per share. Then the value of the shares acquired reconciliation of Rp543 per share. As if seeing the ESOP and MSOP sale of shares by the company during the month of November 2012 stock price MSOP ESOP shares at Rp202 per share. Based on the analysis and realization of sale of shares of ESOP and MSOP stock price of PT MNC Investama. at the time of the closing date of December 31, 2012 amounting to Rp202 per share including the still undervalued. Key words: discounted cash flow, relative valuation, PER (Price Earning Ratio), PBV (Price to Book Value), P/S ratio (Price to Sales Ratio).